A modification of nested PCR method for detection of Enterocytozoon hepatopenaei (EHP) in giant freshwater prawn Macrobrachium rosenbergii - Wang, Yuan; Zhou, Jinyang; Yin, Menghe; Ying, Na; Xiang, Yang; Liu, Wenchang; Ye, Junqiang; Li, Xincang; Fang, Wenhong; Tan, Hongxin (Frontiers in Cellular and Infection Microbiology, 2022)
The microsporidian Enterocytozoon hepatopenaei (EHP) has become a critical threat to the global shrimp aquaculture industry, thus necessitating early detection by screening. Development of a rapid and accurate assay is crucial both for the active surveillance and for the assessment of shrimp with EHP infection. In the present study, a distinct strain of E. hepatopenaei (EHPMr) was found in Macrobrachium rosenbergii. The SWP1 gene analysis revealed it was a new genotype that differed with the common strain isolated from the Litopenaeus vannamei (EHPLv). A nested SWP-PCR method was modified to fix the bug that the original inner primers could not recognize the EHPMr strain. The redesigned inner primers successfully amplified a product of 182 bp for both the EHPMr strain and the EHPLv strain. The new primers also had good specificity and high sensitivity, which may serve as an alternative for EHP genotyping. This study provided a method for detection of EHP in the biosecurity of Macrobrachium rosenbergii farming, and the developed protocol was proposed for the routine investigation and potential carrier screening, especially for molecular epidemiology.